Tools of Legitimacy: The Case of the Petrobras Corporate Blog. Issue 8 (August 2014) - Barros, Marcos
In this paper we explore how organizations are using new social technologies as tools in the discursive struggle over legitimacy. Using critical discourse analysis, we investigate one such struggle between the corporate blog published by Petrobras, Brazil's state-owned oil company, and traditional local newspapers. In this particular battle, Petrobras used several discursive strategies to challenge the media's legitimacy and build its own credibility. Furthermore, we suggest that Petrobras, to underline and to support these strategies, employed a meta-discursive strategy based on a discourse of e-democracy that gave it legitimacy as a discourse producer. In addition, this article contributes to the literature on organizational discourse by uncovering the new social media's characteristic of hyper-intertextuality that was central in transforming the dynamics of power and resistance and the nature of discursive strategies. Our work analyses how organizations can actively and effectively engage these new tools, which embody socially recognized discourses, to create their own discursive arena and legitimate their counter-narratives.